2013
DOI: 10.1136/bmjqs-2013-002097
|View full text |Cite
|
Sign up to set email alerts
|

Managing competing demands through task-switching and multitasking: a multi-setting observational study of 200 clinicians over 1000 hours

Abstract: Despite differences in factors associated with work management strategy use among ED doctors, ward doctors and ward nurses, clinicians in all settings appeared to prioritise certain types of tasks over others. Documentation was generally given low priority in all groups, while the arrival of direct care tasks tended to be treated with high priority. These findings suggest that considerations of safety may be implicit in task-switching and multitasking decisions. Although these strategies have been cast in a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 44 publications
3
62
0
3
Order By: Relevance
“…As ED physicians and nurses interact with many individuals, workflow interruptions create breaks-in tasks4 that are responsible for a considerable amount of multitasking demands in emergency care 7. Our observations revealed that ED staff performed multitasking in approximately a third of the time in line with previous ED studies 3 8 12.…”
Section: Discussionsupporting
confidence: 86%
“…As ED physicians and nurses interact with many individuals, workflow interruptions create breaks-in tasks4 that are responsible for a considerable amount of multitasking demands in emergency care 7. Our observations revealed that ED staff performed multitasking in approximately a third of the time in line with previous ED studies 3 8 12.…”
Section: Discussionsupporting
confidence: 86%
“…Wears and colleagues (2002) describe six environmental features that make the ED particularly complex as compared to other health care settings: 1) an "unbounded" potential for patients, 2) simultaneous evaluation of patients with varying characteristics, 3) high levels of uncertainty, 4) extreme time constraints, 5) lack of feedback regarding level of treatment success, and 6) unpredictable need for risky medical procedure. Although this list is not an exhaustive account of the complexities within the ED, it describes some of the key features that make the ED a particularly complex environment (Wears and Perry, 2002;Walter et al, 2014).…”
Section: The Importance Of Studying Interruptions In the Wildmentioning
confidence: 99%
“…Within healthcare research there is some use of the term multitasking (Chisholm, Collison, Nelson, & Cordell, 2000;Laxmisan et al, 2007;Walter, Li, Dunsmuir, & Westbrook, 2013) where it tends to refer to the clinician's management of, and switching between, multiple threads of responsibility, rather than the clinician's timesharing or rapid switching between tasks at a molecular level. Using Salvucci, Taatgen, and Borst (2009) multitasking continuum, sequential multitasking and switching from one responsibility to another is usually the concern in healthcare (Walter et al, 2013), rather than concurrent multitasking. Sequential multitasking is more likely to be recorded as task switching in response to a series of interruptions.…”
Section: Definitions Of Interruptions and Distractionsmentioning
confidence: 99%